PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS PREZI TERHADAP HASIL BELAJAR SISWA PADA ELEMEN PERALATAN DAN APLIKASI TEKNOLOGI PERKANTORANKELAS X MP DI SMK IMELDA MEDAN T.A 2025/2026 - Erniati Silalahi; Sri Mutmainnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of Grade X Office Management students in the Office Equipment and Office Technology Applications element at SMK Imelda Medan. The problem was caused by the use of teachercentered learning and the dominance of printed learning media, which made students less active and had difficulty understanding the learning material. This study aimed to determine the effect of Prezi-based learning media on students’ learning outcomes in the Office Equipment and Office Technology Applications element. This research employed a quantitative approach using a quasiexperimental method with a non-equivalent control group design. The population consisted of 105 Grade X Office Management students at SMK Imelda Medan in the 2025/2026 academic year. The sample comprised 70 students selected through purposive sampling, consisting of an experimental class using Prezi-based learning media and a control class using printed learning media. Data were collected through pre-test and post-test learning achievement tests and analyzed using the Shapiro– Wilk normality test, Levene’s homogeneity test, and the Independent Sample t-test with SPSS version 26. The results showed that the experimental class achieved a post-test mean score of 78.17, while the control class obtained a mean score of 63.65. The hypothesis testing yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating that the use of Prezi-based learning media had a positive and significant effect on students’ learning outcomes in the Office Equipment and Office Technology Applications element for Grade X Office Management students at SMK Imelda Medan in the 2025/2026 academic year.